PERANAN KONSELING GIZI DALAM PENINGKATAN PENGETAHUAN GIZI DAN KEPATUHAN DIET PASIEN DM - Asmaruddin Pakhri2; Astanti Widiastuti; Manjilala Manjilala (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
ABSTRACT Diabetes Mellitus (DM) is a chronic metabolic disorder due to the pancreas not producing enough insulin or the body cannot use insulin produced effectively. National Riskesdas 2018 results show the prevalence of DM has increased from 6.3% in 2013 to 8.5% in 2018. This study used a pre-experimental method to determine the effectiveness of nutritional counseling on nutritional knowledge and diet compliance of DM patients, with the design of the One Group Pretes - Posttest Design. Samples were adult DM patients who were treated in the inpatient room of Tenriawaru Bone Regional General Hospital who were selected by purposive sampling with a total of 20 DM patients hospitalized and who met the criteria.The results showed the majority of the sample of women (75.0%), aged 41-50 years (35.0%), had a history of past elementary education (60.0%) and did not work ie as an IRT (70.0%), the majority of samples suffer from DM for less than 1 year (35.0%). Nutrition knowledge of good category samples by 8 patients (40.0%) increased to 16 patients (80.0%) after being given nutritional counseling and compliant dietary diet compliance as many as 11 patients (55.0%) increased to 16 patients (80, 0%) after being given nutritional counseling ... There is a significant effect of nutritional counseling on nutritional knowledge and diet compliance of DM patients. It is expected that the hospital will place a nutritionist in each inpatient care room so that each patient can be given nutritional counseling Keywords: Nutritional Counseling, Knowledge, Diet Compliance and Diabetes Mellitus,